Calidad De Vida Y El Equilibrio Dinámico En El Adulto Mayor - Orlando David Mazón Moreno; Pablo Luis Lomas Badillo; Danilo Ortiz Fernández; Santillan Obregon Rodrigo Roberto; Dennys Germán Palacios Valdiviezo (European Scientific Journal, ESJ, 2018)
The objective of the present investigation was to relate quality of life and dynamic balance in older adults. To this end, an intentional sample of older adults was taken from the gerontological centers of Chambo and Guano cantons, for which 35 people make up the control group (Chambo); while 71 people make up the intervention group (Guano). In order to reach the goal of the research, the quality of life was evaluated, through a pre-test called WHOQOL - BREF, followed by the Tinetti test that refers to the march - balance, ending with the Timed get up and go test, which determines the mobility measures of people who can walk on their own. To the intervention group, an exercise program was applied to improve the dynamic balance that lasted ten weeks. Finally, by means of a post test, the entire sample was evaluated, which allowed us to analyze whether there was an incidence. In other words, a slight improvement in both dynamic balance and gait after ten weeks of intervention was evidenced.